Technology Applied A Business Leader's Guide to Software, Systems and IT Projects - Wooldridge, Kevin; Ashurst, Stephen (Routledge, Taylor & Francis Group, 2024)
Technology - love it or hate it - is a critical component for nearly every modern business. To the business leader or aspiring business leader, the world of technology may sometimes appear to be confusing and obscure. The language and nuance of software, systems, and IT projects is often a barrier to effective communication between different parts of an enterprise at just the time when it's most needed - during a technology-enabled project that is seeking to deliver business benefit. This book sets out, in clear non-technical language and with practical real-world examples, the essential background to different aspects of information technology (hardware, software, data, and interfaces); their latest manifestations, such as artificial intelligence and blockchain; and how they all combine into a technology project. Most importantly, this book helps you, the business leader, understand the people behind the technology, appreciate their perspective and their motivations, and to enable you to ask the crucial questions that could transform your engagement to apply technology effectively.
"A Productivity Press Book.". - Online resource; title from PDF title page (Taylor & Francis, viewed June 24, 2024)
Keywords: Business -- Data processing; Gestion; Informatique; BUSINESS & ECONOMICS / Project Management; BUSINESS & ECONOMICS / Information Management